Unveiling the Intellectual Landscape of Artificial Intelligence in Islamic Capital Markets: A PRISMA-Based Systematic Literature Review: Eksplorasi Lanskap Keilmuan Kecerdasan Buatan dalam Pasar Modal Syariah: Studi Tinjauan Literatur Sistematis Berbasis PRISMA - Azwar Azwar; Abur Hamdi Usman; Muh. Riandika; Muh. Rezky Pratama (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2026)
This study aims to systematically map the evolution, intellectual structure, and future research agenda of artificial intelligence (AI) in Islamic capital markets. Employing a Systematic Literature Review (SLR) guided by the PRISMA framework, the study analyzes 34 Scopus-indexed publications to identify temporal trends, dominant themes, methodological developments, and patterns of scholarly collaboration within this emerging field. The findings reveal a clear transformation from a fragmented and pre-paradigmatic stage into a rapidly expanding and increasingly interdisciplinary research domain. Thematically, the literature has evolved from a narrow focus on predictive analytics and efficiency-driven modeling toward a broader integration of risk management, Shariah compliance, sustainability, and behavioral finance. Methodologically, the field has progressed from conventional machine learning techniques to advanced, hybrid, and system-level approaches, reflecting greater engagement with complex financial dynamics. In terms of intellectual structure, the field exhibits a multi-layered and convergent knowledge system supported by globally dispersed, interdisciplinary collaboration networks involving academia, industry, and regulators. Despite these advances, several critical gaps persist, including limited theoretical integration, insufficient development of explainable and Shariah-compliant AI systems, lack of macro-systemic analysis, underexplored applications in social and sustainable finance, fragmented governance frameworks, and weak empirical validation. These findings highlight the need for a paradigmatic shift toward integrative, theory-driven, and impact-oriented research. The study contributes by providing a comprehensive synthesis of the field and proposing a forward-looking research agenda that emphasizes the integration of AI with maqāṣid al-syarī‘ah, ethical governance, and real-world applicability in Islamic capital markets.